Implementasi Kebijakan Pengelolaan Sampah Pada Bank Sampah Mela Meleket Kelurahan Gundaling 1 - Ginting, Hami Br.; Tobing, Artha Lumban; Rajagukguk, Jonson (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2025)
This research aims to determine the implementation of Minister of Environment and Forestry Policy Number 14 of 2021 concerning Waste Management at the Mela Melket Waste Bank, Gundaling District 1. The research meth od used in this research is descriptive qualitative, using implementation theory according to Ripley and Franklin. The results of the research show that the implementation of waste management policies at the Mela Melket waste bank is still not optimal based on the level of compliance and smooth routine, while the performance results of the Mela Melket waste bank have decreased every year, such as an increase in the number of customers, an increase in the amount of waste managed and an increase in the amount of income. The presence of a waste bank can increase public awareness about the importance of managing waste well so that it can have a positive impact on the Gundaling 1 sub-district, such as reducing flooding which is currently a major problem, earning additional income, and keeping the environment safe and healthy.